Role of Thiopurines in Pediatric Inflammatory Bowel Diseases: A Real-Life Prospective Cohort Study. Issue 6 (June 2020) - Atia, Ohad; Ledder, Oren; Ben-Moshe, Tehila; Lev-Tzion, Raffi; Rachmen, Yelana; Meyer, Esther O.; Beeri, Rachel; Renbaum, Pinhas; Shamasneh, Ibrahim; Shteyer, Eyal; Turner, Dan
ABSTRACT: Objectives: Use of thiopurines for inflammatory bowel diseases (IBDs) is declining in some parts of the world. We aimed to explore outcomes of thiopurines and predictors of response in a real-world prospective cohort of children with dose optimization. Methods: Children with IBD treated with thiopurines without biologics were enrolled. Dosing was guided by thiopurine S-methyltransferase-activity at baseline and by clinical response and toxicity at 4 months; 1 year into the study, therapeutic drug monitoring at 4 months was also considered in the decision making. The primary outcome was steroid-free remission without treatment escalation by 12 months (SFR), using the intention-to-treat approach. Results: A total of 129 children were included (74% Crohn disease [CD] and 26% ulcerative colitis [UC]). SFR was achieved in 37 (39%) CD and 13 (39%) UC patients, and SFR with normal erythrocyte sedimentation rate/C-reactive protein in 20 (21%) and 9 (27%), respectively. At 4 months, mean corpuscular volume/white blood cell ratio and Δ absolute neutrophil count weakly correlated with 6-thioguanine ( r  = 0.33, P  = 0.02 and r  = 0.32, P  = 0.02, respectively). In CD, SFR was associated with 4-month median weighted Pediatric Crohn Disease Activity Index (2.5 [IQR 0–7.5] in responders vs 5 in nonresponders [0–12.5], P  = 0.048) and Δabsolute neutrophil count (1.7 [IQR 0.7–4.1] vs 0.05 [−2.3–0.9]; P  = 0.03). Mild drug-related adverse events were recorded in 30 children (22%), 3 required stopping the drug. Conclusions: In this real-life prospective cohort using dose optimization, thiopurines were safe and effective in 21% of CD and 27% of UC patients, including normalization of C-reactive protein and erythrocyte sedimentation rate. Thiopurines remain a viable option in the treatment algorithm of mild-moderate pediatric IBD, especially in girls whose risk for lymphoma is lower. Abstract : Supplemental Digital Content is available in the text